2014
DOI: 10.7314/apjcp.2014.15.13.5233
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects Methylation of FHIT, RASSF1A and RARβ Genes on Non-Small Cell Lung Cancer in the Chinese Population

Abstract: Epigenetic modifications of tumour suppressor genes are involved in all kinds of human cancer. Aberrant promoter methylation is also considered to play an essential role in development of lung cancer, but the pathogenesis remains unclear.We collected the data of 112 subjects, including 56 diagnosed patients with lung cancer and 56 controls without cancer. Methylation of the FHIT, RASSF1A and RAR-β genes in DNA from all samples and the corresponding gene methylation status were assessed using the methylation-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
(50 reference statements)
2
11
0
Order By: Relevance
“…In the past few decades, more and more evidences showed that aberrant DNA methylation, a typical epigenetic modification, had been observed and regarded as a common mechanism leading to inactivation of TSG in cancers (Cancer Genome Atlas Research, 2013;Asiaf et al, 2014;Fang et al, 2014;Li et al, 2014). However, in the previous studies, methylation frequency of RASSF1A gene had been examined only in limited numbers of kidney tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, more and more evidences showed that aberrant DNA methylation, a typical epigenetic modification, had been observed and regarded as a common mechanism leading to inactivation of TSG in cancers (Cancer Genome Atlas Research, 2013;Asiaf et al, 2014;Fang et al, 2014;Li et al, 2014). However, in the previous studies, methylation frequency of RASSF1A gene had been examined only in limited numbers of kidney tumors.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies detected and compared the different rate of RARβ hypermethylation; however, the results were contradictory due to limited number of patients from AC and SCC [3637]. The combining estimates of the odds ratio from 8 publication having 456 SCC and 567 AC is OR = 0.68, 95% CI = 0.52-0.89, p = 0.005, which shows the rate of RARβ hypermethylation was higher in AC than in SCC.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports had proven that methylation of the RAR-β promoter affected numerous tumor-suppressing genes, which were subsequently silent and not expressed (Li et al, 2014). Other researches had indicated the abnormal methylation of RAR-β was associated with early pathogenesis of lung cancer, induced by correlative environmental factor exposure (Maruyama et al, 2002;Lokk et al, 2012;Shaw et al, 2006;Jin et al, 2009;Zhao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The primer sequences (Maruyama et al, 2002;Li et al, 2014), designed to amplify specifically methylated (M) or unmethylated (U) forms of the RAR-β promoter were: M1 (forward) 5'-TCGAGAACGCGAGCGATTC G-3'; M2 (reverse) 5'-GACCAATCCAACCGA AACGA-3'; U1 (forward) 5'-TTGAGAATGTG AGTGATTTGA-3'; U2 (reverse) 5'-AACCAAT CCAACCAAAACAA-3'. The PCR mixture contained 12.5μl TaqMix (Dongsheng, Biotech), 2μl of bisulfitemodified DNA, 1μl 10 pM each primer and 8.5 μl sterile water.…”
Section: Methylation-specific Pcrmentioning
confidence: 99%